Optical soliton solutions of the third-order nonlinear Schrödinger equation in the absence of chromatic dispersion - Ozisik, Muslum; Secer, Aydin; Bayram, Mustafa (WORLD SCIENTIFIC PUBL CO PTE LTD, 2025)
This research paper is dedicated to the investigation of the optical soliton solutions with the power law of self-phase modulation (SPM) and the third-order dispersion (TOD), completely neglecting the chromatic dispersion (CD). The aim is focused on two main points. First, obtaining the straddled soliton solution which permits us to have bright and singular soliton by applying the new Kudryashov (nKM) scheme which was recently introduced as a simple, effective, and reliable method. Second, to observe the influences of the TOD, SPM, and inter-modal dispersion (IMD) on pure-cubic optical soliton dynamics in the absence of the CD.
Keywords: Straddled soliton; pure-cubic optical soliton; bright soliton; inter-modal dispersion; perturbation; GINZBURG-LANDAU EQUATION; PORSEZIAN-DANIEL MODEL; SCHRODINGER-EQUATION; FULL NONLINEARITY; REFRACTIVE-INDEX; KUDRYASHOVS LAW; FIBER; STATIONARY; MOLECULES; Physics